Perancangan Sistem Informasi Perpustakaan SMP Islam Terpadu AL-Qosimiyyah Berbasis WEB - Syndhe Qumaruw Syty (Journal of Research and Publication Innovation, 2024)
Education is the fundamental foundation in shaping human potential, and the integration of information technology has become a key factor in the development of systems. Library service information system emerges as a contemporary solution that not only enhances the administrative efficiency of libraries but also transforms educational services through the utilization of technology. In the world of education, libraries play an integral role in providing learning resources. However, limitations in library service personnel often pose challenges. Therefore, the significant role of the library service information system in improving information accessibility in the educational environment cannot be understated.With a focus on collection management, automation of lending processes, and book search capabilities, this system facilitates user access to literary resources, providing relevant and up-to-date information. The presence of the library service information system not only changes the way libraries operate but also creates a more inclusive and technology-based learning ecosystem. The implementation of the library service information system in educational institutions is not just about administrative efficiency but also about enhancing the learning experience, automating book searches, or borrowing processes. This system illustrates its contribution to achieving better and more adaptive educational services in the digital era.